Active Hybrid Control Algorithm with Sky-Hook Damping and Lead-Lag Phase Compensation for Multi-DOFs Ultra-Low Frequency Active Vibration Isolation System - Min Wang; Xiaoqing Li; Xuedong Chen (Shock and Vibration)
With the improvement of performance in the ultra-precision manufacturing engineering, the requirements for vibration isolation have become more stringent. In order to obtain a wider effective bandwidth and a higher performance of a multi-DOFs active vibration isolation system (AVIS), active hybrid control (AHC) technology is applied in this paper. AHC technology comprises a feedback active control (FBAC) technology and a feedforward active control (FFAC) technology. Absolute velocity feedback is employed to establish a sky-hook damping technology in FBAC technology. Velocity feedforward of base platform is adopted to build a lead-lag phase compensation (LLPC) technology in FFAC technology. Further, a coordinate vector conversion from unit level to system level is mentioned to describe the dynamic characteristic of the six DOFs AVIS applied in the ultra-precision field. And with the assistance of the transformed coordinate vector, the dynamic model of system level is built. Based on the establishment of the dynamic model and the research of AHC, an experimental platform which constitutes three vibration isolators and a real-time active control system is set up. The experimental results indicate that the amplitude of the resonant peak is further reduced significantly, compared to the general feedback control. And simultaneously active effective bandwidth is extended. AHC technology with sky-hook damping algorithm and LLPC control algorithm is verified to be more effective.